SMART organization of construction: indicators of economic modernization and adaptation to environmental risks in modern development - Pokolenko , V.; Sheremet , D.; Lavrinenko , O.; Davydenko , O.; Herasymenko , O. (Ways to Improve Construction Efficiency, 2024)
The article explores the conceptual foundations for implementing SMART management models in construction under the conditions of the industry’s digital transformation, the increasing complexity of the project environment, and growing demands for the efficiency and flexibility of managerial decisions. It substantiates that SMART approaches, based on the principles of specificity, measurability, achievability, relevance, and time-bound orientation, are transforming into a holistic management concept for organizing operational interaction among construction stakeholders. The focus of the research is the integration of digital tools (BIM, ERP, IoT, blockchain, cloud services) into a management system built on adaptive control, risk forecasting, and information transparency.The authors identify key priorities of SMART transformation in operational systems: planning flexibility, digital integration, precision in resource provision, forecasting of costs and timelines, transparency of managerial processes, stakeholder interaction, adaptability to change, quality control, accountability, and risk management. For each of these priorities, relevant KPI indicators are defined, allowing for the formalization and evaluation of managerial decision-making effectiveness at all stages of project implementation. Particular attention is given to the economic-managerial and institutional imperatives of modern risk management, especially the need to integrate risk control into strategic planning, apply intelligent data analysis technologies, and establish institutional interaction between the private and public sectors. It is concluded that SMART construction management models are not only a means of enhancing operational efficiency but also a platform for developing resilient and antifragile enterprises in a dynamic market environment.